Internationalization through exaptation: The role of domestic geographical dispersion in the internationalization process - Santangelo, Grazia D; Stucchi, Tamara (Journal of International Business Studies, 2018)
We introduce the notion of exaptation to internationalization theory, a process in which a capability is re-used for a purpose and in a context different than its historical purpose and context. Specifically, we examine which domestic capabilities may be redeployed when organizations engage in cross-border M&As for the first time. We suggest that organizations exapt (re-use) coordination and control capabilities, initially developed to manage domestic geographical dispersion, to acquire and integrate external resources across borders. By analyzing 693 Indian business groups over a decade, we add to the recent effort to frame the internationalization process within evolutionary theory.